Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/hep.28736
|View full text |Cite
|
Sign up to set email alerts
|

A novel high mobility group box 1 neutralizing chimeric antibody attenuates drug‐induced liver injury and postinjury inflammation in mice

Abstract: Acetaminophen (APAP) overdoses are of major clinical concern. Growing evidence underlines a pathogenic contribution of sterile postinjury inflammation in APAP‐induced acute liver injury (APAP‐ALI) and justifies development of anti‐inflammatory therapies with therapeutic efficacy beyond the therapeutic window of the only current treatment option, N‐acetylcysteine (NAC). The inflammatory mediator, high mobility group box 1 (HMGB1), is a key regulator of a range of liver injury conditions and is elevated in clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 47 publications
4
79
0
Order By: Relevance
“…HMGB1 was discovered over 30 years ago, as an endogenous inflammatory mediator and now serves as a prototype for the class of inflammatory activators tagged as “alarmins” [99]. HMGB1 is a key mediator of inflammation, macrophage proliferation, TNFα production and collagen-I deposition.…”
Section: Key Players In Aldmentioning
confidence: 99%
See 2 more Smart Citations
“…HMGB1 was discovered over 30 years ago, as an endogenous inflammatory mediator and now serves as a prototype for the class of inflammatory activators tagged as “alarmins” [99]. HMGB1 is a key mediator of inflammation, macrophage proliferation, TNFα production and collagen-I deposition.…”
Section: Key Players In Aldmentioning
confidence: 99%
“…HMGB1 can be released either passively by dying cells or actively during an inflammatory response [99] and from LPS-activated macrophages during sepsis [106]. It is normally found in the nucleus but can undergo post-translational modifications and, as a result, it translocates to the cytosol and is ultimately secreted.…”
Section: Key Players In Aldmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, blocking leukocyte DAMP receptors such as toll‐like receptor 9 has shown promise in preclinical models of PCM toxicity . The merits of neutralizing HMGB1 directly have also been demonstrated in animal studies . Expanding the therapeutic repertoire for PCM overdose beyond NAC therefore seems an attainable objective for future research.…”
Section: Managing Paracetamol Overdosementioning
confidence: 99%
“…Pre-clinically, hepatocyte specific HMGB1 ablation has been shown to result in 100 % survival following an APAP dose that is usually lethal in mice [47]. Furthermore, studies have shown that anti-HMGB1 antibodies and knocking out Hmgb1 in the liver reduces hepatic inflammation and liver injury in mouse models of APAP poisoning [43,45,49]. Anti-HMGB1 antibodies are in development for the treatment of human disease [28].…”
Section: High Mobility Group Box Protein 1 (Hmgb1)mentioning
confidence: 99%